Thrombospondin-1 and prolyl 4-hydroxylase subunit alpha 3 as potential biomarkers of salivary gland fibrosis - Zijian Zhang; Honglin Li; Guanru Wang; Guile Zhao; Chunjie Li; Yubin Cao (Elsevier, 2023)
Background/purpose: Fibrosis is present in various physiologic and pathologic conditions of salivary glands (SGs). This study aimed to identify novel biomarkers of SG fibrosis by next-generation sequencing. Materials and methods: We established the SG fibrosis mouse model by excretory main duct ligation. Next-generation sequencing, differentially expressed gene (DEG) analysis, and gene set enrichment analysis was performed by comparing ligated and control SGs. We used algorithms of Cytohubba, molecular complex detection, Lasso logistic regression, and support vector machine to identify the key biomarkers. Selected key biomarkers were verified by the polymerase chain reaction and immunohistochemistry. We also retrieved and analyzed the key gene expression in the fibrosis of the heart, liver, lung, and kidney to ensure the generalization of key biomarkers in SG fibrosis. Results: Both interlobular and intralobular fibrosis was confirmed in the ligated SGs, with improved expressions of collagen I and transforming growth factor β. Next-generation sequencing identified 2666 upregulated DEGs and 336 downregulated DEGs, which were highly enriched in the extracellular matrix-related pathways. Multiple algorithms identified 15 key biomarkers in SG fibrosis, including Thrombospondin-1 (THBS1) and Prolyl 4-Hydroxylase Subunit Alpha 3 (P4HA3). The mRNA and protein expression of THBS1 and P4HA3 was verified in mice. THBS1 was also highly expressed in lung and kidney fibrosis, whereas P4HA3 was upregulated in liver fibrosis. Conclusion: THBS1 and P4HA3 may be potential biomarkers for SG fibrosis. They may be also applicable in the diagnosis of multi-organ fibrosis.